«Гоголевский код» в романе М. Булгакова «Мастер и Маргарита» - Попова-Бондаренко, И.А. (Гоголезнавчі студії, 2008)
В статті проводяться паралелі між романом М. Булгакова “Майстер і Маргарита” та гоголівською прозою. Окреслено деякі загальні та відмінні тенденції мотиву польоту і мотиву голови. Позначені підходи Гоголя та Булгакова до зображення голизни і світу речей. Приділено увагу символіці металів і функції особистих імен. В статье проводятся параллели между романом М. Булгакова «Мастер и Маргарита» и гоголевской прозой. Очерчены некоторые общие и отличные тенденции мотива полёта и мотива головы. Обозначены подходы Гоголя и Булгакова к изображению наготы и мира вещей. Уделено внимание символике металлов и функции личных имён. In the paper parallels between artistic peculiarities of the novel “The Master and Margarita” by M. Bulgakov and the prose by N. Gogol are drawn. Some mutual and different tendencies are outlined concerning the motives of the flight and the head. Gogol’s and Bulgakov’s approaches to the representation of nakedness and of the world of things are designated. The author pays attention to the symbolics of metals and the function of personal names.